Patient Experience of Living With Hemophilia A: A Conceptual Model of Humanistic and Symptomatic Experience in Adolescents, Adults, and Children - Zalmai Hakimi; Rakhee Ghelani; Linda Bystrická; Nana Kragh; Patrick Marquis; Jameel Nazir; Nadine McGale (Journal of Health Economics and Outcomes Research)
**Background:** People living with hemophilia A face challenges impacting their daily lives despite treatment innovations. Previous studies have explored perceptions and treatment experiences; however, there is a lack of an evidence-based, comprehensive model to identify concepts (clinical, physical, and psychological functioning) relevant for people with hemophilia A (PwHA). **Objectives:** The aim of this qualitative study was to address the question: What is the humanistic and symptomatic experience of adolescents, adults, and children living with hemophilia A and what is the impact of hemophilia A on their quality of life? **Methods:** Participants, identified through patient associations in the UK, were male PwHA and caregivers of male PwHA receiving prophylactic treatment. Qualitative research was conducted involving semistructured telephone interviews with PwHA and caregivers between April 2020 and September 2020 in the UK. Standard analytical techniques of conceptual model development were used. **Results:** Of 30 participants, 23 were PwHA and 7 were caregivers. A conceptual model was produced describing patient experience of symptoms, physical functioning, treatment experiences, and the impact of symptoms and treatment on daily lives. Participants reported hemophilia-related symptoms, including bleeding, pain, and joint stiffness, as well as difficulties engaging with social and leisure activities. They also reported protection from bleeds provided by their treatment, relief from symptoms, and the resultant sense of normality. Concepts were broadly relevant across all age groups; however, psychological impacts were reported only by adult PwHA, and caregivers reported impacts related to outdoor activities, play, and education. Participants indicated that their ideal treatment would be delivered orally. **Discussion:** This study highlights the range of symptoms experienced by PwHA across a broad range of age groups, thus enabling the evaluation of relevant concepts across different stages of life. The research supports development of a conceptual model documenting symptoms, impacts, and treatment experience relevant to PwHA. **Conclusion:** Insights gathered through the interviews and resulting conceptual model support development of new therapies to address the physical and social challenges identified by PwHA and highlight a need for novel hemophilia A treatments that can ease treatment administration, provide adequate level of protection, and enable life to be lived normally.